2013
DOI: 10.1155/2013/583598
|View full text |Cite
|
Sign up to set email alerts
|

Central Venous-to-ArterialCO2Gap Is a Useful Parameter in Monitoring Hypovolemia-Caused Altered Oxygen Balance: Animal Study

Abstract: Monitoring hypovolemia is an everyday challenge in critical care, with no consensus on the best indicator or what is the clinically relevant level of hypovolemia. The aim of this experiment was to determine how central venous oxygen saturation (ScvO2) and central venous-to-arterial carbon dioxide difference (CO2 gap) reflect hypovolemia-caused changes in the balance of oxygen delivery and consumption. Anesthetized, ventilated Vietnamese minipigs (n = 10) were given a bolus followed by a continuous infusion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
(44 reference statements)
2
9
0
1
Order By: Relevance
“…In a recent study, aiming to achieve oxygen extraction < 27% as target endpoint, which means keeping ScvO 2 > 73%, reduced the number of organ failures and hospital stay after surgery . In our previous experiments, ScvO 2 showed good correlation with oxygen extraction . However, it is an important finding of the current study that ScvO 2 remained significantly lower at the end of resuscitation as compared with baseline despite that SV has reached its baseline value.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…In a recent study, aiming to achieve oxygen extraction < 27% as target endpoint, which means keeping ScvO 2 > 73%, reduced the number of organ failures and hospital stay after surgery . In our previous experiments, ScvO 2 showed good correlation with oxygen extraction . However, it is an important finding of the current study that ScvO 2 remained significantly lower at the end of resuscitation as compared with baseline despite that SV has reached its baseline value.…”
Section: Discussionsupporting
confidence: 39%
“…This also means that reaching the physiological value of the dCO 2 does not mean adequate tissue oxygenation. In a recent animal experiment, we found that adding dCO 2 to ScvO 2 for predicting hypovolemia‐caused increase of VO 2 /DO 2 > 30% improved positive predictive value from 85% to 100% …”
Section: Discussionmentioning
confidence: 94%
“…5 • 48 In dogs with experimentally induced hypovolemia, low or decreasing Scvo 2 and high or increasing Pcvco 2 -Paco 2 were detected after administration of furosemide, which reflected changes in global oxygen balance and altered microcirculatory blood flow in hypovolemia. 24 As expected in the present study, Sao 2 was significantly higher at all times than was Scvo 2 ; mean Sao 2 over all times was 95 ± 1.7% , which is similar to measurements in healthy neonatal foals reported elsewhere. 49…”
Section: • 24supporting
confidence: 92%
“…Indeed, in patients under general anesthesia the S cv O 2 is often higher than 80%, which is due to the reduced oxygen demand and consumption; hence, higher values should be considered as “normal” [ 30 , 31 ]. Furthermore, in our previous experiments, S cv O 2 showed good correlation with oxygen extraction [ 32 , 33 ]. Therefore, as interpretation of absolute values may prove difficult in different conditions evaluation of the changes of S cv O 2 may be more helpful.…”
Section: Discussionmentioning
confidence: 86%